2019
DOI: 10.3847/1538-4357/aafe81
|View full text |Cite
|
Sign up to set email alerts
|

A Closer Look at Some Gas-phase Depletions in the ISM: Trends for O, Ge, and Kr versus , f(H2), and Starlight Intensity*

Abstract: In a survey of archived ultraviolet spectra of 100 stars recorded by the echelle spectrograph of the Space Telescope Imaging Spectrograph (STIS) on the Hubble Space Telescope (HST), we measure the strengths of the weak absorption features of O I, Ge II and Kr I in the interstellar medium. Our objective is to undertake an investigation that goes beyond earlier abundance studies to see how these elements are influenced independently by three different environmental properties: (1) values of a generalized atomic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 82 publications
0
30
0
Order By: Relevance
“…In fact, we observe sometimes large discrepancies between the observed abundances of the highly volatile elements (e.g. O, Kr, C, N) taken from the literature ( [8], [48], see Extended Data Table 6) on one hand and on the other hand the observed abundances of the mildly volatile elements (e.g. Zn) and the refractory elements, which is hard to interpret with the classic knowledge of dust depletion.…”
Section: The Influence Of Ism Inhomogeneities Along the Line Of Sightmentioning
confidence: 62%
See 1 more Smart Citation
“…In fact, we observe sometimes large discrepancies between the observed abundances of the highly volatile elements (e.g. O, Kr, C, N) taken from the literature ( [8], [48], see Extended Data Table 6) on one hand and on the other hand the observed abundances of the mildly volatile elements (e.g. Zn) and the refractory elements, which is hard to interpret with the classic knowledge of dust depletion.…”
Section: The Influence Of Ism Inhomogeneities Along the Line Of Sightmentioning
confidence: 62%
“…Extended Data Table 6: Column densities of the volatile elements. These values are taken from [8] and [48].…”
Section: Comparing the Metallicity Of Neutral Gas Ionized Gas And Starsmentioning
confidence: 99%
“…Germanium. The gas-phase depletion of Ge was recently measured by both Ritchey et al (2018) and Jenkins (2019), and we obtained from these measurements 𝑓 𝑑 = (67 ± 21)% and (65 ± 20)%, respectively. We take the weighted mean value of these results in our calculations: 𝑓 𝑑 = (66 ± 14)%.…”
Section: Gas-phase Element Depletions and Dust In The Interstellar Me...mentioning
confidence: 64%
“…Argon and Krypton. The abundances of Kr in the cool gas-phase reported in Ritchey et al (2018) and Jenkins (2019) exhibit some depletions with respect to solar values, although the origin of these subsolar abundances remains unclear. Depletions of Ar were also reported, but Sofia & Jenkins (1998) showed that the measurements of the Ar abundance from its neutral form are not always reliable.…”
Section: Gas-phase Element Depletions and Dust In The Interstellar Me...mentioning
confidence: 97%
See 1 more Smart Citation